The Effectivenes of Local Wisdom-Based Science Teaching Materials in Improving High School Students Critical Thinking Skills - Krisianti Ayu Monita; Erlia Narulita; Aris Singgih Budiarso (Universitas Wiralodra, 2021)
In 21st century learning, critical thinking skills are the main choice that must be mastered by students. This study aims to determine the effectiveness of local wisdom-based science teaching materials in improving junior high school students’ critical thinking skills. Most science teachers still apply teacher-centered learning, so students tend to be passive. This type of research is quasi-experimental with a pretest-posttest control group design. The study was conducted in the even semester of the 2019/2020 school year. The subjects of the research were grade VII students. Data collection techniques and instruments in the form of tests that include indicators of critical thinking skills. Data analysis used homogeneity test, Kolmogorov Smirnov normality test, independent sample t-test, and n-gain score. The results of the independent sample t-test are sig. (2-tailed) = 0,000<sig. α = 0.05. Students’ critical thinking skills in the experimental class were higher (N-gain score = 39.09%) than in the control class (N-gain score = 12.03%). Based on the study results, it can be concluded that there is a significant influence on the application of local wisdom-based teaching materials in improving the critical thinking skills of middle school students in the moderate category.